2019
DOI: 10.29173/istl27
|View full text |Cite
|
Sign up to set email alerts
|

Citing of Industry Standards in Scholarly Publications

Abstract: Industry standards are used in many disciplines, including science and technology areas. To date, little research has been conducted regarding the citing of standards in scholarly publications. The aim of this study was to answer two questions: Are standards being cited in scholarly publications? And, if so, what are the characteristics of the publications citing standards? We postulated that the answer to these questions would be of use to science and engineering librarians for collection development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…As Phillips notes, standards are an important part of the engineering design process, and are also useful outside of the engineering field to other professionals and members of the public making informed purchasing decisions [5]. In an analysis of cited standards documents in scholarly literature indexed in the Web of Science database, Rowley and Wagner [6] found that while the vast majority of citations to a selected set of industry standards were from articles in the engineering and materials science disciplines, other science disciplines were represented. The SDOs selected for analysis (ASTM, ISO, and CEN approved) do publish standards that apply to other disciplinary areas, such as CEN/TS 16163:2014, which is concerned with the design of lighting for indoor exhibition displays of cultural heritage objects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As Phillips notes, standards are an important part of the engineering design process, and are also useful outside of the engineering field to other professionals and members of the public making informed purchasing decisions [5]. In an analysis of cited standards documents in scholarly literature indexed in the Web of Science database, Rowley and Wagner [6] found that while the vast majority of citations to a selected set of industry standards were from articles in the engineering and materials science disciplines, other science disciplines were represented. The SDOs selected for analysis (ASTM, ISO, and CEN approved) do publish standards that apply to other disciplinary areas, such as CEN/TS 16163:2014, which is concerned with the design of lighting for indoor exhibition displays of cultural heritage objects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, engineering faculty from a 2011 survey still view journal articles as the most important information source for their students. While engineers in academia certainly cite standards in their own research, as Rowley and Wagner found [17], Cooklev points out a significant challenge concerning standards education is that "in many cases the educators themselves are not familiar with standards and their role" [18]. This disconnect further solidifies the need for additional collaboration between faculty and the librarian, as well as increased integration of the librarian into engineering education courses.…”
Section: Literature Reviewmentioning
confidence: 99%